2003
DOI: 10.2337/diacare.26.4.1224
|View full text |Cite
|
Sign up to set email alerts
|

Do All Prepubertal Years of Diabetes Duration Contribute Equally to Diabetes Complications?

Abstract: OBJECTIVE -This study was designed to explore the timeline of protection against complications in prepubertal children with diabetes, in particular the effects of diabetes duration before age 5 years.RESEARCH DESIGN AND METHODS -In this study, 193 adolescents with prepubertal diabetes onset were followed longitudinally for retinopathy (early background and clinical) and microalbuminuria (albumin excretion rate Ͼ7.5 g/min and Ͼ20 g/min). Multiple logistic regression analysis was used to compare the effect of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
85
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(99 citation statements)
references
References 30 publications
(21 reference statements)
10
85
1
2
Order By: Relevance
“…These results suggest that the presence of ICAs and IAAs at diagnosis does not influence the development of complications. Rather, known predictors of microvascular complications include longer diabetes duration, especially for the prepubertal years with diabetes and health care utilization (47)(48)(49). The association of higher GAD titer levels at diagnosis with pupillary abnormalities is consistent with the previous report of higher titers at the time of diagnosis of peripheral neuropathy (45).…”
Section: Tpoas and Development Of Thyroid Diseasesupporting
confidence: 81%
See 1 more Smart Citation
“…These results suggest that the presence of ICAs and IAAs at diagnosis does not influence the development of complications. Rather, known predictors of microvascular complications include longer diabetes duration, especially for the prepubertal years with diabetes and health care utilization (47)(48)(49). The association of higher GAD titer levels at diagnosis with pupillary abnormalities is consistent with the previous report of higher titers at the time of diagnosis of peripheral neuropathy (45).…”
Section: Tpoas and Development Of Thyroid Diseasesupporting
confidence: 81%
“…Celiac disease was confirmed by small-bowel biopsy and was offered to all patients with positive AGA or EMA titers. Screening for microvascular complications was undertaken 3.1-13.4 years after diagnosis at the Children's Hospital at Westmead and included assessments of retinopathy, nephropathy, and autonomic and peripheral neuropathy (47)(48)(49)(50). Retinopathy was defined as the presence of at least one microaneurysm or hemorrhage in at least one eye detected by seven-field stereoscopic fundal photography (48).…”
Section: Research Design and Methods -From A New Southmentioning
confidence: 99%
“…In our study, microalbuminuria was delayed by very early onset of diabetes and confirmed these previous prospective studies (14,31,32). We do not suggest that poor metabolic control in prepubertal children does not add to the risk of microvascular complications, but there is evidence that it does so at a lower rate (33).…”
Section: Figure 3-influence Of A1c On Development Of Microalbuminuriasupporting
confidence: 79%
“…The reason for this observation remains unclear, suggesting other factors being involved in the regulation of adiponectin secretion Table 2 Correlation analysis for associations between serum adiponectin levels and lipid concentrations in children, adolescents and young adults with type 1 diabetes. (31)(32)(33)(34)(35). In addition, gender differences in the prevalence of atherosclerosis in type 1 diabetes could possibly be explained by the observed findings during puberty.…”
Section: Discussionmentioning
confidence: 97%